Analisis Pengaruh Return On Investment (ROI), Return On Equity (ROE), dan Debt To Equity Ratio (DER) Terhadap Harga Saham Pada Perusahaan Tekstil dan Garmen, Tbk Yang Terdaftar Di Bursa Efek Indonesia - Erviva Fariantin (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
This study aims to examine the effect of Return On Investment (ROI), Return On Equity (ROE) and Debt to Equity Ratio (DER) on Stock Prices in Textile and Garment Companies, Tbk. listed on the Indonesia Stock Exchange for the period 2011-2017. The research variable consisted of 3 (three) independent variables and 1 (one) dependent variable. This type of research is associative research.The population in the study amounted to 17 companies with the sampling technique using purposive sampling so that the number of samples was 13 companies. The criteria for sampling are all Textile and Garment companies, Tbk. who issued a complete financial report for the period 2011-2017. The results showed partially that all independent variables (ROI, ROE and DER) had no effect on stock prices, but simultaneously the independent variables (ROI, ROE and DER) had an effect on stock prices.